2004
DOI: 10.1007/s11837-004-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

TiBw-reinforced Ti composites: Processing, properties, application prospects, and research needs

Abstract: Editor's Note: A hypertext-enhanced version of this article is available on-line at www.tms.org/pubs/journals/JOM/0405/Chandran-0405.html.Discontinuously reinforced titaniumtitanium boride whisker (TiB w ) composites are becoming a commercial reality for a number of demanding automotive, aerospace, and other advanced applications. This article presents the general microstructural characteristics and mechanical properties of Ti-TiB w composites of various matrix compositions and TiB w volume fractions based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(114 citation statements)
references
References 11 publications
1
109
0
4
Order By: Relevance
“…This can be explained by the different contributions to the macroscopic increase in hardness by the individual phases. With respect to the microhardness of the reinforcements, values reported in the literature are lower for TiB (~1800 HV0.1) than for TiC (~3200 HV0.1) [45]. For the latter, hardness did indeed exhibit a slight correlation with stoichiometry, and declined by roughly 15-20% while decreasing the C/Ti ratio to ~0.5.…”
Section: Structural Characterizationmentioning
confidence: 78%
“…This can be explained by the different contributions to the macroscopic increase in hardness by the individual phases. With respect to the microhardness of the reinforcements, values reported in the literature are lower for TiB (~1800 HV0.1) than for TiC (~3200 HV0.1) [45]. For the latter, hardness did indeed exhibit a slight correlation with stoichiometry, and declined by roughly 15-20% while decreasing the C/Ti ratio to ~0.5.…”
Section: Structural Characterizationmentioning
confidence: 78%
“…Titanium alloys can be reinforced by TiB 2 , TiN, B 4 C, ZrC, TiB, TiC, and Al 2 O 3 [6]. Among various reinforcements, TiB seems to be the most attractive option because it has a close to titanium density, high Young's modulus and reasonable stability at the processing temperatures [11,12]. In addition, TiB creates minimal residual stresses due to similarity of thermal expansion coefficient and good crystallographic interfaces with the titanium matrix [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among various reinforcements, TiB seems to be the most attractive option because it has a close to titanium density, high Young's modulus and reasonable stability at the processing temperatures [11,12]. In addition, TiB creates minimal residual stresses due to similarity of thermal expansion coefficient and good crystallographic interfaces with the titanium matrix [11][12][13]. The effect of TiB on the strength properties of Ti-based matrix was either as good as, if not better than, most widely used reinforcements such as TiC or Al 2 O 3 [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,25,26) The significant increase in strength and stiffness in boron-modified Ti alloys arise from the strong and stiff TiB whiskers that precipitate in-situ during solidification. 3,23) Due to the similarity of the thermal expansion coefficients (8:6 Â 10 À6 /K for Ti and 7:5 Â 10 À6 /K for TiB 21) ), only small residual stresses result at the TiB/Ti interface, which does not exhibit significant reactivity, 30) after the cooldown from processing. In addition, recent work has shown that the addition of small amounts ($0:1 mass%) of B to a Ti-6Al-4V(mass%) alloy decreases the as-cast grain size by approximately an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%